2015
DOI: 10.1017/s1368980014003036
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childhood adversity and food insecurity: ‘It’s like a bird nesting in your head’

Abstract: Objective: Adverse childhood experiences, including abuse, neglect and household instability, affect lifelong health and economic potential. The present study investigates how adverse childhood experiences are associated with food insecurity by exploring caregivers' perceptions of the impact of their childhood adversity on educational attainment, employment and mental health. Design: Semi-structured audio-recorded in-person interviews that included (i) quantitative measures of maternal and child health, advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 58 publications
3
66
0
Order By: Relevance
“…In addition, there is the utilitarian hypothesis alluded to in the introduction according to which women exposed to violence and mental distress have more trouble getting and sustaining jobs or finishing school. Opportunities and adequate income thus progressively decrease, with insufficient diet ensuing as a long-term end result (10,47) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is the utilitarian hypothesis alluded to in the introduction according to which women exposed to violence and mental distress have more trouble getting and sustaining jobs or finishing school. Opportunities and adequate income thus progressively decrease, with insufficient diet ensuing as a long-term end result (10,47) .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other research that has been done on this association (Lent et al, 2009). Further, maternal mental health has been directly linked to domestic violence exposure and other Adverse Childhood Experiences (Chilton et al, 2015; Chilton et al, 2014). In fact, Hernandez and colleagues (2014) showed that the association between exposure to interpersonal violence and household food insecurity at a 2-year follow-up was mediated by maternal depression.…”
Section: Food Insecurity and Parental Mental Healthmentioning
confidence: 99%
“…13,14 Finally, parent ACEs may contribute to vulnerable living conditions, such as food insecurity, 13,15 as well as higher risk of ACEs among the children themselves. 16,17 The potential intergenerational effects of ACEs are supported by research revealing increased risk of adverse health outcomes among children of parents who experienced chronic trauma. 8 Yet, authors of almost no studies have examined whether parent ACEs are related to the health of their children, particularly beyond infancy.…”
mentioning
confidence: 99%